Human Fetal Tissue Transplantation - Bhattacharya, Niranjan; Stubblefield, Phillip; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Over the past decade there have been major advances in the field of regenerative medicine with the promise to bring to reality, cures for debilitating diseases such as diabetes, heart failure, and Parkinson$1 (Bs disease. Cellular products from a variety of sources are being evaluated for their ability to replace damaged tissue. Fetal tissues consist of stem cells and progenitor cells which have undergone initial commitment with varying states of differentiation. Stem cells from fetal tissues may also have a greater proliferative potential than their adult counterparts. In addition, fetal derived stem and progenitor cells are immunologically naive and some sources of fetal cells, eg cord blood, have been shown to be capable of crossing greater HLA mismatching resulting in less rejection and decreased immune mediated toxicities. Given the increasing focus on HES and advances in our basic knowledge of regenerative medicine it is an appropriate time to review the biology and use of fetal tissues. Human Fetal Tissue Transplantation is a timely publication that provides details of many aspects of the potential use of fetal tissues for therapeutic applications. As many tissues are wasted on a daily basis it appropriate to raise discussion on how to maximize access to discard tissue and at the same time engage in discussion of the ethics associated with fetal tissue procurement and clinical use.s
Part I The ideas behind this book -- Part II Basic Science and the unique aspect of fetal growth and maturation -- Part III Fetal Cell transplant experiments in animal and human systems -- Part IV Fetal tissue transplant experiments in animal and human systems -- Part V Fetal Organ transplant experiments in animal and human systems -- Part VI Biobanking -- Ethics of fetal tissue transplant.
Keywords: Medicine; Hematology; Pathology; Medicine & Public Health; Hematology; Pathology